Social Distancing Membawa dampak Terhadap Interaksi Sosial di Masyarakat - Berea Angeline Thelessy Adi Putri; Gayu Konita; Satrio Dwi Laksono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Social distancing as a measure to prevent the spread of disease has significantly changed the paradigm of social interaction in society. The impact is visible in various aspects of daily life, including interpersonal relationships, social activities, and community dynamics. This research discusses the impact of social distancing on social interactions in society. First, social distancing practices change the way individuals communicate. Physical restrictions have caused a shift from face-to-face interactions to virtual interactions via digital platforms. Although technology has made connectivity possible, some people have difficulty expressing emotions and building deep relationships in virtual environments. Second, social distancing also affects people's social life. Social events which are usually places for meetings and cultural exchanges have had to be canceled or adjusted to comply with health protocol regulations. This can cause a breakdown in social ties and a lack of sense of solidarity among community members. Apart from that, the economic impact can also be felt socially. Restrictions on economic activities result in reduced incomes and increased uncertainty, which can trigger stress and tension in social relationships. Economically vulnerable groups of society suffer more from these restrictions. In this context, it is important for society to find new ways to establish and maintain healthy social relationships. Strengthening virtual communication, innovation in social activities, and mental support are the keys to overcoming the negative impact of social distancing on social interactions in society. Adopting a qualitative approach, this research involves in-depth interviews, participant observation, and social media content analysis to understand changes in interaction patterns as social distancing is implemented. Key findings include paradigm shifts in forms of social interaction, psychological impacts on individuals, and adaptation strategies used by society to maintain connectivity. The results of this research provide in-depth insight into the dynamics of social change amidst the pandemic, providing a basis for formulating better policies in dealing with similar situations in the future. By documenting people's experiences, this research has the potential to contribute to our collective understanding of social adaptation during crises in society.